Reforming MSWM in Sukunan (Yogjakarta, Indonesia): A case-study of applying a zero-waste approach based on circular economy paradigm. (15th February 2021) - Kurniawan, Tonni Agustiono; Avtar, Ram; Singh, Deepak; Xue, Wenchao; Dzarfan Othman, Mohd Hafiz; Hwang, Goh Hui; Iswanto, Iswanto; Albadarin, Ahmad B.; Kern, Axel Olaf
Abstract: Over the past years, Indonesia, the world's fourth most populous country, has confronted environmental problems due to uncontrolled generation of municipal solid waste (MSW). While the integrated solid waste management (ISWM) represents a critical strategy for Indonesia to control its production, it is also recognized that economic approaches also need to be promoted to address the waste problem concertedly. In this case study, empirical approaches are developed to understand how a volume-based waste fee could be incorporated into MSW collection services and how to apply a zero-waste approach in Indonesia by adapting resource recovery initiatives, adapted from Germany's mature experiences in integrating the CE paradigm into the latter's MSWM practices. Currently, Sukunan village (Yogyakarta, Indonesia) promotes waste reduction at sources in the framework of community-based solid waste management (CBSWM) by mobilizing the local community for waste separation (organic and non-organic) and waste recycling. As a result, about 0.2 million Mt of CO2-eq emissions was avoided annually from local landfills. The economic benefits of recycling activities by the village's community also resulted in 30% reduction of the waste generated. This CBSWM scheme not only saves the government budget on waste collection, transport and disposal, but also extends the lifetime of local landfills as the final disposal sites. By integrating the CE paradigm into its MSWM practices through the implementation of economic instruments and adherence to the rule of law in the same way as Germany does, Indonesia could make positive changes to its environmental policy and regulation of MSW. A sound MSWM in Indonesia could play important roles in promoting the effectiveness of urban development with resource recovery approaches to facilitate its transition towards a CE nationwide in the long-term. Graphical abstract: Image 1 Highlights: Germany is an ideal role model for Indonesia to adopt a circular economy paradigm. Resource recovery in Sukunan balances environmental protection and economic growth. Sukunan village reduced waste generation by incorporating ISWM and resource recovery. Implementation of circular economy in Sukunan led to 30% reduction of the waste. About 0.2 million Mt of CO2-eq emissions was avoided from local landfills.